PEMBERIAN MOL KEONG MAS DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL KACANG NAGARA DI LAHAN GAMBUT - Toria Magistra; Raihani Wahdah; Noor Aidawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This research aims to examine the effect of the interaction of golden snail MOL with chicken manure on the growth and yield of nagara bean plants and to examine the best combination of golden snail MOL and chicken manure on the growth and yield of nagara bean plants. This research used a factorial randomized block design (RAK) consisting of 2 factors and 3 replications. The first factor of the MOL dose for golden snails consists of 4 levels, m1 = 5 ml L-1 : m2 = 10 ml L-1 : m3 = 15 ml L-1 : m4 = 20 ml L-1. The second factor of chicken manure dosage (K) consists of 4 levels, k0 = 0 t ha-1 :k1 = 5 t ha-1 :k2 = 10 t ha-1 :k3 = 15 t ha-1. The results of the study showed that there was no interaction between golden snail MOL and chicken manure on all observed parameters. The single factor of giving MOL golden snails had a significant effect on the variable height of plants aged 4, 7, 13, and 14 WAP. Providing higher concentrations of golden snail MOL (20 and 15 ml L-1) had a good effect on the growth of nagara bean plants. The single factor of giving chicken manure had a significant effect on the variables of plant height aged 11, 12, 13, and 14 WAP, weight of 100 seeds, seed yield per plant, and plant yield per hectare. Providing chicken manure at a rate of 15 t ha-1 had a good effect on plant height, number of seeds, weight of 100 seeds, seed yield, yield per plant, and yield per hectare.